2021
DOI: 10.1186/s40494-021-00503-6
|View full text |Cite
|
Sign up to set email alerts
|

Scratching the surface: the use of sheepskin parchment to deter textual erasure in early modern legal deeds

Abstract: Historic legal deeds are one of the most abundant resources in British archives, but also one of the most neglected. Despite the millions that survive, we know remarkably little about their manufacture, including the species of animal on which they were written. Here we present the species identification of 645 sixteenth–twentieth century skins via peptide mass fingerprinting (ZooMS), demonstrating the preferential use of sheepskin parchment. We argue that alongside their abundance and low cost, the use of she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Over the past decade, ZooMS has been used to answer a wide range of cultural heritage, archaeological, ecological, and paleontological questions. For example, ZooMS has been used to study the manufacture of worked bones, artifacts, and cultural heritage materials ,,,,,, and to better characterize archaeological faunal assemblages and past human–animal relationships. ,,,,, It has been used to better define past domestic animal management strategies, ,, document the introduction of commensal species associated with human activities, and identify the exploitation of wild species. ,,, It has contributed to the reconstruction of past ecologies ,,,,, and to the study of extinct megafauna. , ZooMS has also been notably used as a low-cost, high-throughput screening tool of bone fragments in large Pleistocene cave sequences, leading to the discovery of otherwise nondiagnostic hominid remains, ,,, including the offspring of a Neanderthal mother and Denisovan father. , Finally, because ZooMS can be performed using minimally invasive sampling techniques, ,,, it has proven a breakthrough technology in the emerging field of biocodicology, the multidisciplinary analysis of parchment manuscripts, codices, and other historic documents. ,, …”
Section: Applications In Paleoproteomicsmentioning
confidence: 99%
“…Over the past decade, ZooMS has been used to answer a wide range of cultural heritage, archaeological, ecological, and paleontological questions. For example, ZooMS has been used to study the manufacture of worked bones, artifacts, and cultural heritage materials ,,,,,, and to better characterize archaeological faunal assemblages and past human–animal relationships. ,,,,, It has been used to better define past domestic animal management strategies, ,, document the introduction of commensal species associated with human activities, and identify the exploitation of wild species. ,,, It has contributed to the reconstruction of past ecologies ,,,,, and to the study of extinct megafauna. , ZooMS has also been notably used as a low-cost, high-throughput screening tool of bone fragments in large Pleistocene cave sequences, leading to the discovery of otherwise nondiagnostic hominid remains, ,,, including the offspring of a Neanderthal mother and Denisovan father. , Finally, because ZooMS can be performed using minimally invasive sampling techniques, ,,, it has proven a breakthrough technology in the emerging field of biocodicology, the multidisciplinary analysis of parchment manuscripts, codices, and other historic documents. ,, …”
Section: Applications In Paleoproteomicsmentioning
confidence: 99%
“…Species identification via peptide mass fingerprinting, presented in Doherty et al 52 , identified 622 (96.4%) as sheep ( Ovis aries ), whilst the remaining 23 (3.6%) could be classified as sheep or goat ( Capra aegagrus hircus ) as separation between the species was not possible due to a lack of diagnostic peptides. Sheepskin was preferentially used over goat of calfskin ( Bos taurus ) for the production of legal documents from the twelfth century onwards in England, Wales and Ireland due to its susceptibility to delaminate when scrapped serving to deter fraudulent textual erasure and modification 52 . No British legal deed has been identified as goatskin through biomolecular analysis 52 , 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Sheepskin was preferentially used over goat of calfskin ( Bos taurus ) for the production of legal documents from the twelfth century onwards in England, Wales and Ireland due to its susceptibility to delaminate when scrapped serving to deter fraudulent textual erasure and modification 52 . No British legal deed has been identified as goatskin through biomolecular analysis 52 , 53 . It is therefore highly likely that these 23 skins are from sheep and as such were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, certain animal skins were probably used deliberately, either because of price differences or because of their practical utility. For example, legal deeds from thirteenth to twentieth century in the United Kingdom were probably mostly made of sheepskin because fraudulent changes can be more easily traced on it [ 189 ]. Furthermore, proteomics analyses are suitable for the investigation of illuminated manuscripts and inks since these were often produced with proteinaceous binders and glues, e.g., from the egg yolk and/or egg white of various birds, as well as from gelatin, collagen, or milk of various animals and certain plants, e.g., gum arabic [ 12 , 190 ].…”
Section: Paleoproteomics and Metaproteomics Analysesmentioning
confidence: 99%